SIMULATION OF VERTICAL WATER FLOW THROUGH VADOSE ZONE (Nigerian Journal of Technology, 2017)
Simulation of vertical water flow representing the release of water from the vadose zone to the aquifer of surroundings within Nigerian Defence Academy (34km2) for a sustainable ground water resources management was carried out using Advanced Simulation and Modelling of Urban Ground Water Management (UGROW model).Rainfall data, soil moisture and runoff coefficient are specified as input data into the model. Basic component of the vertical water balance (precipitation, leakages, evaporation and runoff)was observed. From the results, 4.0cm/day of average leakage observed for the period 1991-2001 was the maximum leakage for the simulation. http://dx.doi.org/10.4314/njt.v36i4.42